The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1115/1.4049810
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: “Electro-Osmotic Propulsion of Jeffrey Fluid in a Ciliated Channel Under the Effect of Nonlinear Radiation and Heat Source/Sink,” [ASME Journal of Biomechanical Engineering, 2021, 143(5), p. 051008; DOI: 10.1115/1.4049810]

Abstract: Mathematical modelling of mechanical system in microfluidics is an emerging area of interest in micro scale engineering. Since microfluidic devices use the hair like structure of artificial cilia for pumping, mixing and sensing in different fields, therefore; electro osmotic cilia driven flow help to generate the fluid velocity for the Newtonian and viscoelastic fluid. Due to the deployment of artificial ciliated walls, the present research reports the combined effect of an electro osmotic flow and convective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Similarly, Akram et al [15] explored the effects of Joule heating on the electro-osmotic peristaltic flow of TiO 2 /10W40 nanofluid in a curved microchannel. Some similar studies can be found in [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 62%
“…Similarly, Akram et al [15] explored the effects of Joule heating on the electro-osmotic peristaltic flow of TiO 2 /10W40 nanofluid in a curved microchannel. Some similar studies can be found in [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 62%
“…Recently, Saleem et al [ 128 ] numerically analyzed the transportation of thermally radiated nanofluid in the microchannel in which the inside layer was settled with artificial cilia. In similar physical conditions, parameters such as electric potential, directional flow, velocity, pressure, temperature, and entropy generation were numerically analyzed by the same group [ 129 , 130 , 131 ]. Outside osmotic pumps, a numerical study [ 132 ] was reported to examine the heat transfer in the rectangular channel under the influence of the mechanical stirrer or artificial cilia.…”
Section: Artificial Cilia For Microfluidic Applicationsmentioning
confidence: 99%
“…A numerical model has been proposed for the time-subordinate ciliary propulsion of a limited micro-organism by Rao [5]. It can been concluded in the light of observations of various experiments that biological fluids possesses non-Newtonian nature [6][7][8][9][10][11][12][13], and [14]. A simple Newtonian fluid does not represent true picture of physiological fluids.…”
Section: Introductionmentioning
confidence: 99%